Improving Science and Social Studies Learning Outcomes in Grade 5 through the Inquiry Learning Model Assisted by Interactive Multimedia - Mahendra, Febrian; Rizqillah, Ahmad Fajar Ridho; Asrulloh, Anil Fahrizin; Siswoyo, Andika Adinanda (Actual Insight, 2025)
This study addresses the low academic performance of fifth-grade students at Gili Timur 2 Public Elementary School in understanding the solar system topic within the Natural and Social Sciences curriculum. The problem was attributed to conventional teaching methods and the minimal use of visual media. This research aimed to enhance student learning outcomes by implementing an inquiry-based learning model integrated with interactive multimedia using Morph PowerPoint. The study adopted a Classroom Action Research design following the Kemmis and McTaggart model and was conducted in three cycles involving 39 students. Data collection techniques included observations, interviews, and achievement tests, with all instruments validated prior to use. The findings demonstrated a significant improvement in student achievement, with average scores increasing from 59.08 in Cycle I to 79.38 in Cycle II and 83.85 in Cycle III. The percentage of students achieving mastery learning also rose markedly from 23.07% to 97.43%. The integration of inquiry-based instruction with Morph PowerPoint effectively enhanced students’ conceptual understanding, engagement, and motivation. This study offers a pedagogical contribution by demonstrating the potential of combining Morph PowerPoint with inquiry-based learning in elementary science education a synergy that has received limited attention in existing research. Nevertheless, challenges such as limited instructional time and diverse student learning preferences should be addressed for broader application.